Lilium longiflorum Plant Growth with a combination of Naphthylacetic Acid (NAA) and 6Benzylaminopurine (BAP) In Vitro - Fauziah, Rosita Husnun; Kusmiyati, Florentina; Anwar, Syaiful (Universitas Muhammadiyah Malang, 2019)
This research was aim to identify the effect of Naphthylacetic Acid (NAA) and 6-Benzylaminopurin (BAP) on growth of Lilium longiflorum planlet. The research method was Completely Randomized Design Factorial 4 x 4 with 4 replication. First factor was concentration of NAA, consist of A0: 0 mg/l, A1: 0,75 mg/l, A2: 1,5 mg/l, and A3: 2,25 mg/l. Second factor was concentration of BAP, consist of : B0: 0 mg/l, B1: 0,3 mg/l, B2: 0,6 mg/l, and B3: 0,9 mg/l. The observed parameters were number of shoots, plant height, number of leaves, number of roots, and percentage of contamination. Data were process by Analysis of Variance and continued by Least Significance Different (LSD). The result showed that combination of NAA and BAP did not significantly affect the growth parameter of Lilium longiflorum. BAP treatment significantly affected the number of shoots and number of leaves. The number of roots only observed in NAA treatment; 0,3 mg/l BAP + 0,75 mg/l NAA; 0,3 mg/l BAP + 1,5 mg/l NAA; and 0,6 mg/l BAP + 0,75 mg/l NAA. Percentage of fungal contamination was 7,5%. The conclusion of the result were the treatment 0f 0,3 mg/l BAP + 0,75 mg/l NAA was the best treatment for growth of Lilium longiflorum planlets with no contamination.